Synchronous Hodgkin's lymphoma and seminoma: a rare coexistence and an important lesson. Issue 10 (30th August 2017) - Singh, Prabhsimranjot; Toom, Sudhamshi; Shrivastava, Makhardwaj; Shaw, Jason; Silver, David; Balderacchi, Jasminka; Lipshitz, Jay
Key Clinical Message: Synchronous presentation of seminoma and lymphoma is rare but has important ramifications for the treatment of both malignancies. Without clinical vigilance, this situation may be easily missed, leading to inappropriate management. We describe a patient with synchronous seminoma and Hodgkin's lymphoma and discuss the implication on his treatment. Abstract : Synchronous presentation of seminoma and lymphoma is rare but has important ramifications for the treatment of both malignancies. Without clinical vigilance, this situation may be easily missed, leading to inappropriate management. We describe a patient with synchronous seminoma and Hodgkin's lymphoma and discuss the implication on his treatment.